Teatro fuori di sé. Sul lavoro di Wanda Golonka - Müller-Schöll, Nikolaus (Kritik. Rivista di letteratura e critica culturale, 2024)
Since Klaus Michael Grüber’s work on Euripides’ Bacchae at Berlin’s Schaubühne in the 1970s, there has perhaps not been a more radical attempt than that of director Wanda Golonka’s An Antigone to investigate the foreignness and at the same time the closeness of the material of a Greek myth or tragedy in the setting of a public theater by making it jump. The choice of Antigone should come as no surprise. Nowhere else are the political issues raised by Golonka’s behavior within the institutional theater discussed so radically as in this tragedy: the act of freedom in relation to the law; the transgression that does not represent a questioning of the individual law, but rather exhibits the fragile foundation of law, provokes a crisis of the existing order and its legitimacy, taking upon itself the responsibility for the violation, with all the consequences that follow. It is no coincidence that this moment of stepping “outside oneself” has been repeatedly discussed in connection with this work